Foundations of Demography are Theoretical, Population Geography, Scientific and Practical Foundations and Concepts (Eurasian Journal of Humanities and Social Sciences, 2022)
This article outlines the scientific practical foundations of demography, the scientific practical foundations of demogtaphism, the essence of the concept of demogtaphism, the basis and laws of study of demography, development, demographic processes, population reconstruction, birth within demographic processes are important aspects of demographics